2022
DOI: 10.2991/assehr.k.211125.132
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Voices on Implementing Blended Synchronous Learning in Teaching Genre-Based Writing

Abstract: Implementing blended learning in teaching students' genre-based writing had doneat Universitas Muhammadiyah Semarang (Unimus) for almost three years by employing the integration between asynchronous learning and synchronous learning through some platforms. Specialty, in this pandemic situation, the blended learning is developed becomes Blended Synchronous Learning (BSL) bycombining virtual face to face and online learning. To scrutinize how the implementation of BSL on teaching students' genre-based writing ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…For instance, some researchers found that a genre-based approach enhances the students' writing skills (Dong & Lu, 2020;Herman et al, 2020;Irawansyah, 2016;Pham & Bui, 2021). Wijayatiningsih et al (2021) pointed out that genre-based writing courses explained that writing was a complex skill and required stages of creating a coherent text. Simultaneously, the genrebased approach stands out as a precise method for understanding various types of texts.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some researchers found that a genre-based approach enhances the students' writing skills (Dong & Lu, 2020;Herman et al, 2020;Irawansyah, 2016;Pham & Bui, 2021). Wijayatiningsih et al (2021) pointed out that genre-based writing courses explained that writing was a complex skill and required stages of creating a coherent text. Simultaneously, the genrebased approach stands out as a precise method for understanding various types of texts.…”
Section: Introductionmentioning
confidence: 99%
“…English Education lecturers in Indonesia have responded to technological advances in the digital 5.0 era, so they have changed classroom learning from face-to-face to integrated faceto-face online, especially in writing (Wilson, 2020;Wijayatiningsih et al, 2021;& Maulida, 2020). Because they may not repeat material in face-to-face classes, a weakness of the faceto-face learning paradigm (Sun & Chen, 2016;Wright, 2017;Santikarn & Wichadee, 2018).…”
Section: Introductionmentioning
confidence: 99%